ความชุก และปัจจัยที่สัมพันธ์กับภาวะวิตกกังวล และซึมเศร้าในผู้ป่วยมะเร็งลำไส้ใหญ่และทวารหนักที่มีทวารเทียมทางหน้าท้องในโรงพยาบาลจุฬาลงกรณ์ สภากาชาดไทย - วิลาสินี พิพัฒน์ผล (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this cross-sectional descriptive study was to estimate the prevalence and associated factors of anxiety and depression in colorectal cancer patients after colostomy surgery at King Chulalongkorn Memorial Hospital. Data were collected from 80 patients with colorectal cancer after colostomy surgery at Out-Patient Department of Surgery, King Chulalongkorn Memorial Hospital from May to October 2014. Self-report included:1) Demographic data and medical history; 2) Self-esteem questionnaire; 3) The Personal Resource Questionnaire; 4) Thai Hospital anxiety and depression scale (Thai-HADS) All these were complete by the patients. The data were analyzed by percentage, mean, standard deviation, Chi-Square test, Pearson’s correlation and multivariate logistic regression analysis to predict associated factors with anxiety and depression in colorectal cancer colostomy patients. A p-value of less than 0.05 was considered statistically significant. The results showed that the prevalence of anxiety in colorectal cancer colostomy patients were 35 percent and the prevalence of depression in colorectal cancer colostomy patients were 10 percent. The statistically significant factors associated with anxiety were age, duration of illness, duration of colostomy surgery, socialization, self-esteem and social support. Self-esteem and social support were significantly associated with depression. In multivariate regression analysis, statistically significant factors associated with anxiety were aged 60 years or more (OR=5.07; 95%CI=1.57-16.42), duration of illness less than 6 months (OR=5.19; 95%CI=1.14-23.64) and duration of colostomy surgery less than 3 months (OR=4.96, 95%CI=1.58-15.58), but can’t do regression analysis to find factors associated with depression because limited assumption of study was found 8 patients with depression. Self-esteem and social support were associated with anxiety and depression in colorectal cancer colostomy patients. Self-esteem should be respected and social support given for post colostomy surgery colorectal cancer patients in order to decrease anxiety and depression.